3D printing of magnesium-containing biomedical materials for bone repairment towards actual applications - Jiang, Shan; Zhang, Jiazhen; Tian, Tian; You, Mingyu; Qu, Chunge; Li, Yaohua (Frontiers in Materials, 2025)
The integration of biodegradable magnesium (Mg)-containing materials with additive manufacturing technologies has opened promising avenues for next-generation biomedical implants. Owing to their unique combination of biodegradability and mechanical compatibility with bone, Mg alloys and composites have emerged as candidates for temporary orthopedic and cardiovascular devices. This review critically examines recent progress in 3D printing of Mg-containing biomaterials, with a focus on material design, fabrication strategies, and translational pathways toward clinical application. We analyze the performance of leading additive manufacturing techniques—including Selective Laser Melting (SLM), Wire Arc Additive Manufacturing (WAAM), Binder Jetting (BJAM), and 3D Gel Printing (3DGP) in tailoring biocompatibility and mechanical behavior to meet clinical demands. Beyond conventional material assessments, this review also identifies critical challenges in evaluating customized 3D printed implants, emphasizing the need for adapted regulatory and testing frameworks. By mapping advances from laboratory research to clinical translation, this review underscores the transformative potential of 3D printing Mg-containing biodegradable implants in bone repair. With their advantages to provide temporary support, stimulate osteogenesis, and gradually resorb without secondary surgery, Mg-containing constructs represent a cornerstone for the future of customized and sustainable implant technologies.